2016
DOI: 10.1158/1535-7163.mct-15-0892
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of F877L and T878A Mutations on Androgen Receptor Response to Enzalutamide

Abstract: Treatment-induced mutations in the ligand-binding domain of the androgen receptor (AR) are known to change antagonists into agonists. Recently, the F877L mutation has been described to convert enzalutamide into an agonist. This mutation was seen to co-occur in the endogenous AR allele of LNCaP cells, next to the T878A mutation. Here, we studied the effects of enzalutamide on the F877L and T878A mutants, as well as the double-mutant AR (F877L/T878A). Molecular modeling revealed favorable structural changes in t… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
67
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 80 publications
(68 citation statements)
references
References 48 publications
0
67
1
Order By: Relevance
“…Additional studies to further dissect the differential recruitment of NCoR1 and its impact on androgen signaling will help to better understand the significance of this mutation for prostate cancer progression. An altered recruitment of coregulators has previously been reported for AR H875Y treated with DHT and the AR F877L/T878A double mutant bound by enzalutamide . Interestingly, altered transcriptomes and cofactor recruitment profiles have also been documented for clinically relevant estrogen receptor mutants …”
Section: Discussionmentioning
confidence: 69%
See 1 more Smart Citation
“…Additional studies to further dissect the differential recruitment of NCoR1 and its impact on androgen signaling will help to better understand the significance of this mutation for prostate cancer progression. An altered recruitment of coregulators has previously been reported for AR H875Y treated with DHT and the AR F877L/T878A double mutant bound by enzalutamide . Interestingly, altered transcriptomes and cofactor recruitment profiles have also been documented for clinically relevant estrogen receptor mutants …”
Section: Discussionmentioning
confidence: 69%
“…1b) while giving special care to the preserved interaction of the cyano group of the CF 3 -/Clsubstituted benzonitrile moiety to R753, which was identified as key interaction in other structural and modeling studies. 36 Inspection of the proposed binding mode of darolutamide to the antagonistic AR wild type conformer suggested a face-toface stacking interaction of the eastern pyrazole moiety to the indole group of W742 (Fig. 1c).…”
Section: Structural Interpretation Of the Darolutamide Antagonistic Pmentioning
confidence: 99%
“…Mutations in the ligand-binding domain that alter ligand specificity and sensitivity frequently increase after androgen ablation. The AR F877L mutation has been found in enzalutamide resistant patients and might allow for enzalutamide acting as an AR antagonist, especially when this mutation co-occurs with the T878A mutation in prostate cancer cells (3133). Prolonged enzalutamide or apalutamide treatment might reposition the drug to eliminate steric clashes that promoted helix 12 terminus (H12) dislocation in AR (34).…”
Section: Discussionmentioning
confidence: 99%
“…The current more intensive androgen deprivation treatments in CRPC, including abiraterone or enzalutamide, may thereby further select for gain-of-function AR mutations to allow the restoration of AR signaling in tumor cells. Recent studies on PCa cell lines and patient samples have revealed multiple AR point mutations, including treatment-induced F877L and T878A [8, 10, 29, 30]. The majority of these mutations occur within the LBD domain and function to alter the ligand binding specificity of AR.…”
Section: Discussionmentioning
confidence: 99%